Detecção e caracterização gênica de rotavírus de pacientes atendidos em hospitais públicos infantis da cidade de Manaus, Amazonas, entre os anos de 2007 e 2008 - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The human gastroenteritis are among the diseases of greatest public health impact worldwide. There are several etiologic agents of diarrhea, with emphasis rotavirus, viral pathogen prominently in the genesis of severe acute gastroenteritis in childhood, accounting for over 450,000 deaths in children worldwide. The rotavirus genome consists of a 11 segment of double stranded RNA encoding six structural proteins (VPs) and five nonstructural proteins (NSPs). Classification of rotavirus serotypes and genotypes is based on the epitopes of the glycoprotein VP7 neutralized, called G, and VP4 protease-sensitive protein called P, which generates a binary classification scheme G and P. Epidemiological studies of molecular characterization of genes encoding for proteins of rotavirus are essential for assessing the effectiveness of the vaccine Rotarix (GlaxoSmithKline), introduced in Brazil since 2006, in addition to assessing the possible emergence of new viral genotypes. The aim of this study was to identify and characterize genes of rotavirus in feces of children with diarrhea in Manaus between the years 2007 and 2008. 1337 samples were collected from diarrheal children under 10 years old in the city of Manaus, between the years 2007 and 2008. There was a percentage of 5.4% of positive samples for rotavirus. Viral genotypes were identified through polymerase chain reactions preceded by reverse transcription. The genotype G2P[4] was found in 93% of cases, followed by G [NT-untyped] P4 in 6% and G2P[9] 1% of the samples. Among the 73 samples detected in this study, 58 were eligible for the current vaccine. Phylogenetic analysis revealed a pattern of clustering of gene sequences into clusters that showed similarity with samples from Belém (Brazil) and China.
Keywords: Doença Diarreica; Rotavírus; Epidemiologia; Caracterização Molecular; CIÊNCIAS DA SAÚDE